Software and Algorithmic Aspects of Parallel Calculation of Non-Isothermal Moisture Transfer in Fractal-Structure Materials - Sokolovskyy, Yaroslav; Yarkun, Volodymyr; Levkovych, Mar'iana; Storozhuk, Oleksandr; Kapran, Ihor (International Conference on Perspective Technologies and Methods in MEMS Design (Online), 2021)
A new mathematical model of the nonstationary process of heat and moisture transfer in the two-dimensional region is constructed on the basis of the use of Kaputo and Grunwald-Letnikov derivatives. An implicit finite-difference scheme for approximation of a mathematical model of noisothermal moisture transfer taking into account the fractional integro-differential apparatus is developed. The given algorithm of numerical realization of model allows to receive values of function of temperature and humidity for all points of area of partition. The method of fractional steps is adapted for numerical realization of mathematical model. It allowed performing parallel calculations of two difference half-step taking into account the corresponding spatial coordinate. An analysis of parallel solutions on multi-core computers has been performed. The software a parallel algorithm using .Net threads and algorithmic features of the TPL library has developed. It has been tested on multi-core computer systems with CPUs of different capacities. The analysis of acceleration and efficiency of the algorithm on the basis of the constructed graphs is carried out.